Young Indonesian Muslim Women (Not) Only Pursue Piety - Haganta, Karunia (Muslim Politics Review, 2024)
Pious Girls: Young Muslim Women in Indonesia by Annisa R. Beta (London: Routledge, 2024) This book is a comprehensive initial study of the ideal construction of young Muslim women in Indonesia. In the Introduction, Annisa positions the ideal of young Muslim women in Indonesia not as something singular, but rather in contestation. This contestation has implications for at least two perspectives, which are seen further in the following chapters of this book. First, there are many ideals and constructions of young Muslim women, all of which are related to the socio-political conditions of society from at least three aspects: religious practice, market logic, and political life. Second, apart from through the contestation between existing constructions, young Muslim women themselves show their agency by defining these constructions and ideals themselves.